A survey of student loan burden among United States Chiropractors: Insights on debt, relief, and educational value - Samuel M. Schut; Zachary A. Cupler; Brian C. Coleman (PLoS ONE, 2026)
Background Although student loans have made health professional education accessible for a greater proportion of the US population, rising student indebtedness has incited considerable discourse. This study aimed to characterize US chiropractors’ self-reported student loan debt, student loan relief opportunities, and perceived value of chiropractic training. Methods A 38-item cross-sectional, anonymous, electronic survey was developed. Chiropractors who graduated from a US-based, Council on Chiropractic Education-accredited Doctor of Chiropractic program (DCP) were recruited. The survey was conducted between February 2025 to March 2025. Survey domains included (1) demographics, (2) financial characteristics, (3) loan relief, and (4) educational and career value. Descriptive statistics and visualizations were used for analysis. Results A total of 1,455 responses were collected. The mean (SD) and median (Q1-Q3) student loan debt at graduation was $176,297 ($89,460) and $185,000 ($120,000–$240,000). At survey completion, 85% retained student loan debt, averaging $232,062 ($102,691) with a median of $240,000 ($177,500–$290,000). Mean (SD) gross income in 2023 was $99,068 ($100,349); median (Q1-Q3) was $76,000 ($50,000-$115,000). Approximately 87% of respondents reported being ineligible or unsure about eligibility for loan relief programs. Over half (53.3%) disagreed or strongly disagreed that their DCP provided a positive return on investment (ROI), and approximately 70% rated the financial ROI of DCP training as low or very low. Perceptions of non-financial ROI were more favorable. Overall, 65% would not choose a chiropractic career again; among them, 67.3% would pursue a career in another healthcare field. Conclusions US chiropractors are burdened with considerable student loan debt that outpaces gross income. The findings of this study are commensurate with prior studies investigating chiropractic educational debt, yet likely are not unique to the profession and represent larger challenges faced by many modern US health professions. Innovation is likely needed to support the sustainability of the chiropractic profession given tension between educational debt and income.